Nutrition Therapy in Elderly with Chronic Obstructive Pulmonary Disease (COPD) - Fasitasari, Minidian (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Nutrition is an important health element for elderly people and influence aging process. Malnutrition prevalence is increasing in this population. Chronic Obstructive Pulmonary Disease (COPD) is one of the chronic diseases in elderly that is related to malnutrition. The association between malnutrition and pulmonary disease (including COPD) has been known for a long time. Malnutrition has negative impacts on pulmonary structure, elasticity, and function, strength and endurance of respiratory muscles, pulmonary immunity defense mechanism, and breath control. Inversely, pulmonary disease (including COPD) will increase energy need and may reduce dietary intake. Nutrition intervention in COPD patient is intended for regulating anorexia, improving pulmonary function, and controlling weight loss. Nutrient requirements will be calculated according to the results of nutrition assessment. This article will discuss about nutrition therapy in elderly with COPD. It describes respiratory system in aging, association COPD and nutrition, and nutrition assessment, as well as nutrition intervention in elderly people with COPD.